Sustainability of cities: conceptual aspects - Araújo, Maria Luiza Malucelli (UFPR, 2006)
The attempt to conciliate nature protection and its use isconsidered as a challenge to sustainability in the currentcontext. There are different criteria and concepts to be appliedso the environmental challenge becomes an opportunity ratherthan a factor generating unsustainability within cities. In orderto achieve the ideals of urban sustainability, social andenvironmental concerns must be conjugated, based onintegrated policies. Furthermore, it must be considered thatdue to the multiplicity of the involved agents, social issuessuch as health, employment and housing cannot be set aside.The question that is placed than is if it is possible to speak interms of sustainable cities, or if sustainability surpasses theboundaries of cities, whose social and space relations alreadyhave exceeded the municipal scale.